Interlaboratory Comparison of Methods Determining the Botanical Composition of Animal Feed. (23rd November 2019) - Braglia, Luca; Morello, Laura; Gavazzi, Floriana; Gianì, Silvia; Mastromauro, Francesco; Breviario, Diego; Cardoso, Hélia Guerra; Valadas, Vera; Campos, Maria Doroteia
Abstract: A consortium of European enterprises and research institutions has been engaged in the Feed-Code Project with the aim of addressing the requirements stated in European Union Regulation No. 767/2009, concerning market placement and use of feed of known and ascertained botanical composition. Accordingly, an interlaboratory trial was set up to compare the performance of different assays based either on optical microscope or DNA analysis for the qualitative and quantitative identification of the composition of compound animal feeds. A tubulin-based polymorphism method, on which the Feed-Code platform was developed, provided the most accurate results. The present study highlights the need for the performance of ring trials for the determination of the botanical composition of animal feeds and raises an alarm on the actual status of analytical inaccuracy.